KELAYAKAN USAHA DAN NILAI TAMBAH AGROINDUSTRI TEMPE - Winanti Puspa Arum; Sudarma Widjaya; Lina Marlina (Lampung University, 2017)
The purpose of this research is to evaluate the feasibility and the added value of tempe agroindustry. This research uses a case study method on Barkah’s agroindustry (big production scale) and Muklisin’s agroindustry (medium production scale) at Podomoro village and Hamsin’s agroindustry (small production scale) at South Pringsewu village in Pringsewu Subdistrict, Pringsewu Regency. Research location is chosen purposively based on the quantity of production and same age of agroindustry. Analysis data uses quantitative and qualitative descriptive. The result of this research showed that tempe agroindustry at various scales of production (big, medium, small) in general was profitable and feasible to be developed. Tempe agroindustry in this research provided high enough added value, although still using relatively simple technology and limited capital. Key words: added value, agroindustry, feasibility, tempe